Characterization and comparative analysis of toxin–antitoxin systems in Acetobacter pasteurianus. (1st June 2019) - Xia, Kai; Bao, Han; Zhang, Fuming; Linhardt, Robert J; Liang, Xinle
Abstract: Bacterial toxin–antitoxin (TA) systems play important roles in diverse cellular regulatory processes. Here, we characterize three putative type II TA candidates from Acetobacter pasteurianus and investigate the profile of type II TA systems in the genus Acetobacter . Based on the gene structure and activity detection, two-pairs loci were identified as the canonical hicAB and higAB TA systems, respectively, and DB34_01190 – DB34_01195 as a putative new one without a canonical TA architecture. Physiologically, the expression of the three pairs conferred E. coli with additional plasmid maintenance and survival when under acetic acid stress. Chromosomal TA systems can be horizontally transferred within an ecological vinegar microbiota by co-option, and there was a tendency for toxin module loss. The antitoxin retention in the genome is suggested to have a broad role in bacterial physiology. Furthermore, A. pasteurianus strains, universally domesticated and used for industrial vinegar fermentation, showed a higher number of type II TA loci compared to the host-associated ones. The amount of TA loci per genome showed little positive relationship to insertion sequences, although its prevalence was species-associated, to the extent of even being strain-associated. The TA system is a candidate of studying the resistant mechanistic network, the TAs-dependent translatome affords a real-time profile to explore stress adaptation of A. pasteurianus, promoting industrial development.